A STUDY OF FLY ASH OF TALCHER (MAHANADI BASIN) & SINGARENI (GODAVARI BASIN) COALS OF INDIA - ch, Dr.Anil Babu. (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Thousands of coal fired thermal power plants working all over the world. These are to produce electricity, leaving coal ash as waste. The coal ash produced every day is not taken seriously in the beginning .But now with few millions of tons of ash being generated every day, the disposal of ash is the burning problem of today for the scientists all over the World. As the other energy sources are limited, usage of coal is increasing year after year. Hence more attention is paid on the usage of coal ash. In this coal ash, the bottom ash left in the boiler will be about 20%. The remaining is the fly ash collected through the electrostatic precipitators. So the importance of fly ash. This fly ash problem is more in India due to high (40%) ash content of the Indian coals so the problem of chemistry and management of fly ash has been taken up. The microscopic, X-ray, chemical, engineering and beneficiation studies were identified.With regards to ashes we have deliberately chosen the captive thermal power plant of Visakhapatnam steel plant as it uses the coal from Talcher coal Fields. The Talcher coal fields are in north India (Orissa state) and formed in the Mahanadi river basin. To represent a south India coal field the captive thermal power plant of Kothagudem is choosen which gets coal from the Singareni coal fields formed in the Godavari river basin in Andhra Pradesh state.